Preparation of oxygen-electric bifunctional electrocatalysts by low-temperature molten salt method and their application in zinc-air batteries
The preparation of oxygen-electric dual-function electrocatalysts by zinc chloride and sodium chloride dual eutectic low-temperature molten salt method has solved the problems of poor activity of existing carbon material catalysts in zinc-air batteries and complex preparation process, and achieved efficient and stable positive electrode performance of zinc-air batteries.
Patent Information
- Application Number
- CN202211071424.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-09-02
AI Technical Summary
Existing carbon material catalysts show poor bifunctional catalytic activity in zinc-empty batteries, cumbersome preparation process and easy attenuation under alkaline conditions.
The oxygen-electric dual-function electrocatalyst is prepared by zinc chloride and sodium chloride bi-eutectic low-temperature molten salt method. By annealing under the protection of an inert gas and washing with deionized water, a three-dimensional carbon nanosphere material with a high specific surface area and rich pores is formed, and metal sulfide is loaded thereon.
The dual-functional activity of oxygen reduction reaction (OER) and oxygen precipitation reaction (ORR) is achieved, which significantly improves the open circuit voltage and peak power density of the positive electrode of the zinc-empty battery, and has excellent charging and discharge cycle stability, which is suitable for large-scale production.
Smart Images

Figure 220901180836 
Figure 220901180839 
Figure 220901180841
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy environment and nanomaterials, and specifically relates to a low-temperature molten salt method for preparing a high specific surface area and high activity oxygen-electric bifunctional electrocatalyst for a high-stability zinc-air battery positive electrode. Background Art
[0002] The abuse of fossil fuels will lead to energy resource shortages and environmental pollution. There is an urgent need to develop and utilize green and sustainable energy. Currently, lithium-ion batteries are at the forefront of energy storage. The theoretical energy density of lithium-ion batteries is about 400Wh kg −1 The insufficient energy density seriously hinders its application in some fields that require high energy density power sources. In contrast, zinc-air batteries have low cost, no pollution and high theoretical energy density (1086Wh kg -1 However, the inherent slow reaction kinetics of oxygen reduction reaction and oxygen evolution reaction lead to poor charge and discharge capacity and low efficiency. When it is prepared as the positive electrode of liquid zinc-air battery, the cycle stability is poor.
[0003] Precious metals such as platinum group metals (PGM), iridium oxide (IrO2), and ruthenium oxide (RuO2) catalysts are currently the most effective catalysts, but their single catalytic function, high cost, poor long-term stability, and scarcity seriously hinder their large-scale commercialization. In view of this, it is crucial to develop alternatives with high activity, durability, and low cost. Transition metal catalysts have become a research hotspot for current scientific researchers because of their good electrochemical activity, low cost, and abundant resources. Among them, iron-based carbon material catalysts are considered to be the most promising alternatives to precious metal catalysts because of their excellent catalytic activity. They have been widely studied in recent years and have made rapid progress.
[0004] Three-dimensional carbon nanosphere material is an ideal structure with a large specific surface area, which can expose more active sites and has a unique three-dimensional structure. Since electrochemical catalytic reactions usually occur on the surface of materials, a larger specific surface area can expose more active sites and provide a faster charge transfer pathway. Zinc chloride and sodium chloride can help form porous carbon structures at high temperatures, and can effectively preserve nitrogen-enhanced N dopants. As a semi-closed reactor, low-temperature molten salt can effectively promote the decomposition of intermediate substances and uniform metal doping during the pyrolysis of carbon materials. The volatilization of zinc cations in the ionic liquid during the annealing process of zinc chloride and sodium chloride plays an important role in the porosity of carbon materials, thereby obtaining a larger specific surface area, and zinc sulfide can also be attached to the carbon matrix to form active species. However, nowadays, the preparation process of carbon material catalyst materials is cumbersome, time-consuming and labor-intensive, the synthesis process is highly polluting, poorly tolerant, and only has a single catalytic performance, which limits its application in high-performance zinc-air battery positive electrodes. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects and shortcomings of the prior art carbon material catalysts, such as poor bifunctional catalytic activity, cumbersome preparation and easy attenuation under alkaline conditions, and the defects of insufficient stability when applied to zinc-air batteries. In view of this, a method for oxygen-electric bifunctional electrocatalyst is provided, which has the advantages of low equipment requirements, low cost of required raw materials, easy control of reaction conditions, simple preparation method, complete functions, high efficiency, low cost and good stability, and can be used for bifunctional electrocatalysts of OER and ORR. The prepared catalyst is used for the positive electrode of zinc-air battery.
[0006] The object of the present invention is to provide an oxygen-electric bifunctional electrocatalyst.
[0007] Another object of the present invention is to provide the application of the above oxygen-electric bifunctional electrocatalyst in the positive electrode of a high-performance zinc-air battery.
[0008] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0009] The steps include:
[0010] S1: zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0011] S2: weighing the metal-containing carbon source and sulfur source in sequence and mixing them evenly, weighing zinc chloride and sodium chloride, adding them to the mixture and mixing them evenly again to obtain a precursor with uniform color;
[0012] S3: annealing the uniformly mixed precursor obtained by grinding at 700-1000° C. for 1-3 h under the protection of an inert gas to obtain a high-temperature solid product;
[0013] S4: The high-temperature solid product is fully washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0014] S5: The prepared bifunctional catalyst, water, ethanol and Nafion are mixed in a certain proportion to form a slurry, which is then coated on a conductive substrate for use as the positive electrode of a zinc-air battery.
[0015] Furthermore, in step S1, zinc chloride and sodium chloride have dual functions, namely, serving as carbon material carriers, and zinc cations also serve as reactants to participate in the reaction to form zinc sulfide, and the ratio of zinc chloride to sodium chloride is 1-10:1-10.
[0016] Furthermore, the metal-containing carbon source in step S2 is at least one or more of iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate and manganese acetylacetonate.
[0017] Furthermore, the sulfur source in step S2 is at least one sulfur-containing organic compound such as thiourea, methionine, and sodium dodecyl sulfate.
[0018] Furthermore, the mass ratio of the metal-containing carbon source, sulfur source, zinc chloride and sodium chloride in step S2 is: 0.1-1: 0.1-2: 1-10: 1-10 (wherein the units of the metal-containing carbon source, sulfur source, zinc chloride and sodium chloride are g).
[0019] Furthermore, the inert gas in step S3 is one of nitrogen, argon or helium.
[0020] Furthermore, in step S3, the annealing heating rate is 2-15°C / min, the temperature is raised to 700-1000°C, and the temperature is kept for 1-3h.
[0021] Furthermore, the product obtained after the water washing in step S4 is three-dimensional hollow carbon nanospheres.
[0022] Furthermore, in step S5, the ratio of the catalyst, water, ethanol, and Nafion is 2-10:500-1500:500-1500:30-100 (wherein the unit of the catalyst is mg, and the unit of water, ethanol, and Nafion is μL).
[0023] Furthermore, the conductive substrate to be coated in step S5 is one of carbon cloth, carbon paper, nickel foam and copper foam.
[0024] The present invention also provides that the zinc chloride and sodium chloride not only provide a liquid space at high temperature, but also the zinc cation in the zinc chloride acts as a pore-forming agent when volatilizing, so that the catalyst has a larger specific surface area and abundant pores.
[0025] The present invention also provides an oxygen-electric bifunctional electrocatalyst prepared by the preparation method.
[0026] The present invention also provides the use of the oxygen-electricity bifunctional electrocatalyst in preparing a high-performance zinc-air battery positive electrode.
[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0028] (1) The oxygen-electric bifunctional electrocatalyst described in the present invention adopts zinc chloride and sodium chloride binary eutectic salt to assist semi-closed carbonization to prepare a high-density active catalyst. The precursor is pyrolyzed under the protection of zinc chloride and sodium chloride binary eutectic salt, which not only provides a space for ionic liquid confinement, but also plays a key role in regulating the porous structure and specific surface area of the catalyst. The zinc cations in zinc chloride will also form zinc sulfide loaded on the three-dimensional carbon carrier. It has a large specific surface area and rich pore structure. The bifunctional catalyst electrocatalyst is annealed at high temperature to obtain a carbon nanosphere material with a unique three-dimensional structure co-doped with nitrogen and sulfur, and the zinc ions in zinc chloride will form zinc sulfide loaded on the carbon nanosphere at high temperature. The synergistic effect makes it have good oxygen reduction performance and oxygen precipitation performance, and excellent conductivity. It is then prepared into a slurry for use in the positive electrode of a zinc-air battery with a large open circuit voltage and a peak power density of 196mW / cm 2 , has excellent charge-discharge cycle stability, and can be cycled for more than 4,000 cycles. The preparation process of the present invention is simple, low in cost, requires little equipment investment, is suitable for large-scale production, and has good industrial prospects. In the preparation process, no toxic or harmful organic or inorganic substances are involved, and no toxic or harmful substances are generated. It is green and environmentally friendly, and is conducive to the application of the bifunctional electrocatalyst in high-performance zinc-air batteries and other batteries.
[0029] (2) The oxygen-electric bifunctional electrocatalyst described in the present invention has a distinct three-dimensional spherical structure. Compared with existing catalysts, the bifunctional catalyst has good catalytic properties, good tolerance under alkaline conditions, methanol resistance, corrosion resistance, large specific surface area, and multiple active sites. It is green and pollution-free and has both ORR and OER functions, which is beneficial to the preparation of zinc-air batteries and can be more widely used in various catalyst batteries.
[0030] (3) The present invention prepares the oxygen-electric bifunctional electrocatalyst by a low-temperature molten salt method. The preparation method is simple to operate, the materials are readily available, no toxic or harmful organic or inorganic substances are involved, and no toxic or harmful substances are generated, so it is non-toxic and pollution-free. It only requires simple mixing of raw materials, so it is low-cost, has good universality, and is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 11 is a phase diagram of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0032] Figure 2 This is a scanning electron microscope image of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0033] Figure 3 This is the X-ray diffraction pattern of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0034] Figure 4 This is a transmission electron microscopy image of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0035] Figure 5 This is a diagram showing the nitrogen absorption and desorption of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0036] Figure 6 This is the ORR polarization curve of the oxygen-R bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0037] Figure 7 This is an ORR polarization curve diagram of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention after acid washing and etching.
[0038] Figure 8 This is the OER polarization curve of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0039] Fig. 9 This is a graph showing the ORR stability test of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention.
[0040] Fig.10 This is an open circuit voltage performance diagram of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention used in a liquid zinc-air battery.
[0041] Fig.11 This is a discharge polarization curve diagram of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention used in a liquid zinc-air battery.
[0042] Fig.12 This is a diagram showing the rechargeable cycle stability performance of the oxygen-electric bifunctional electrocatalyst prepared in Example 2 of the present invention for use in a liquid zinc-air battery. DETAILED DESCRIPTION
[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0044] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] Example 1
[0048] The preparation process of the oxygen-electric bifunctional electrocatalyst of the present invention comprises the following steps:
[0049] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0050] (2) Weigh 0.1-1g of a carbon source containing metal and 0.1-2g of a sulfur source in sequence and mix them until the color is sufficiently uniform. Then, weigh 1-10g of zinc chloride and sodium chloride and add them to mix evenly to obtain a precursor with uniform color.
[0051] (3) annealing the mixture solid in a tube furnace under the protection of an inert gas such as argon, nitrogen or helium, at an annealing heating rate of 2-15°C / min, heating to 700-1000°C, and keeping the temperature for 1-3 hours to obtain a high-temperature black solid;
[0052] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0053] (5) 2-10 mg of the prepared bifunctional catalyst, 500-1500 μL of water, 500-1500 μL of ethanol, and 30-100 μL of Nafion are mixed to form a slurry, which is then applied on a conductive substrate for use as the positive electrode of a zinc-air battery.
[0054] The carbon source of the metal-containing carbon source is at least one of ferric acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate and manganese acetylacetonate, or a mixture of two thereof. The sulfur source is at least one of sulfur-containing organic compounds such as thiourea, methionine, and sodium dodecyl sulfate. The conductive substrate is one of carbon cloth, carbon paper, nickel foam, and copper foam.
[0055] The zinc chloride and sodium chloride of the present invention have dual functions. First, the zinc chloride and sodium chloride form a semi-enclosed carbonized ionic liquid-constrained space at high temperature. Second, the zinc cation in the zinc chloride volatilizes at high temperature and acts as a pore-forming agent.
[0056] The oxygen-electric bifunctional electrocatalyst of the present invention has a large specific surface area, which can reach 500-1000m 2 / g, the pore size distribution is relatively rich, and metal sulfides (zinc sulfide, iron sulfide) are loaded on the three-dimensional carbon nanospheres. The synergistic effect between them and the carbon materials makes it have excellent OER / ORR dual functional activity.
[0057] The oxygen-electricity bifunctional electrocatalyst of the present invention can be applied to high-performance zinc-air batteries, has good catalytic activity and high stability, has a large open circuit voltage and a high power density, and has readily available raw materials, simple preparation, is green and pollution-free, and is suitable for large-scale production.
[0058] Example 2
[0059] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0060] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0061] (2) Weigh 1 g of ferric acetylacetonate and 1 g of thiourea respectively and mix them until the color is fully uniform. Weigh 3 g of sodium chloride again and mix them. Finally, weigh 7 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0062] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0063] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0064] (5) 5 mg of the prepared bifunctional catalyst, 980 μL of water, 980 μL of ethanol, and 40 μL of Nafion were mixed to form a slurry, which was then coated on carbon paper for use as the positive electrode of a zinc-air battery.
[0065] The sodium chloride / zinc chloride phase diagram shows that the molten salt will turn into an ionic liquid as the temperature rises. The semi-closed state of this ionic liquid can be used as a fluid template for carbon precursors. When the temperature rises, the volatilization of zinc cations in zinc chloride can effectively form pores, increasing its specific surface area, which can be confirmed by nitrogen adsorption and desorption analysis tests.
[0066] The prepared oxygen-electric bifunctional electrocatalyst was subjected to scanning electron microscopy analysis, X-ray diffraction analysis, nitrogen adsorption-desorption analysis, ORR, OER, ORR stability test, zinc-air battery open circuit voltage test, zinc-air battery discharge polarization performance test, and zinc-air battery charge and discharge cycle stability test.
[0067] The results are as follows Figure 1-Figure 12 As shown, the image of the oxygen-electric bifunctional electrocatalyst is composed of peaks of FeS, ZnS, and C. The OER / ORR bifunctional electrocatalyst has an obvious three-dimensional carbon nanosphere structure, and the FeS and ZnS metal nanoparticles are distributed on the three-dimensional carbon nanospheres in the TEM test.
[0068] After the FeS and ZnS metal nanoparticles were pickled and etched away, the ORR performance was significantly reduced, which indicates that the synergistic effect of FeS, ZnS metal nanoparticles and carbon nanospheres improved the catalytic performance of the catalyst. The prepared bifunctional electrocatalyst has a higher open circuit voltage, better power density, and excellent charge and discharge cycle stability (4000 cycles) when used for the positive electrode of zinc-air batteries.
[0069] Example 3
[0070] In this embodiment, the preparation process of the oxygen-to-R bifunctional electrocatalyst includes the following steps:
[0071] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0072] (2) Weigh 0.2 g of ferric acetylacetonate and 1.8 g of sodium dodecyl sulfate respectively and mix them until the color is sufficiently uniform. Weigh 5 g of sodium chloride again and mix them. Finally, weigh 5 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0073] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0074] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0075] (5) 6 mg of the prepared bifunctional catalyst, 1000 μL of water, 1000 μL of ethanol, and 60 μL of Nafion were mixed to form a slurry, which was then coated on carbon cloth for use as the positive electrode of a zinc-air battery.
[0076] Example 4
[0077] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0078] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0079] (2) Weigh 1.2 g of nickel acetylacetonate and 0.8 g of methionine in sequence and mix until the color is fully uniform, then weigh 7 g of sodium chloride and mix again, and finally weigh 3 g of zinc chloride and add to mix thoroughly to form a solid mixture with uniform color;
[0080] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0081] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0082] (5) 10 mg of the prepared bifunctional catalyst, 500 μL of water, 500 μL of ethanol, and 100 μL of Nafion were mixed to form a slurry, which was then applied on copper foam for use as the positive electrode of a zinc-air battery.
[0083] Example 5
[0084] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0085] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0086] (2) Weigh 1.5 g of ferric acetylacetonate and 1 g of methionine respectively and mix them until the color is fully uniform. Weigh 1 g of sodium chloride again and mix them. Finally, weigh 9 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0087] (3) annealing the mixture solid in a tube furnace under the protection of inert gas nitrogen, with an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0088] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0089] (5) 8 mg of the prepared bifunctional catalyst, 1200 μL of water, 1200 μL of ethanol, and 80 μL of Nafion were mixed to form a slurry, which was then coated on carbon paper for use as the positive electrode of a zinc-air battery.
[0090] Example 6
[0091] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0092] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0093] (2) Weigh 0.1 g of nickel acetylacetonate and 0.8 g of thiourea respectively and mix them until the color is fully uniform. Weigh 2.2 g of sodium chloride again and mix them. Finally, weigh 5.5 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0094] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0095] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0096] (5) 5 mg of the prepared bifunctional catalyst, 880 μL of water, 980 μL of ethanol, and 50 μL of Nafion were mixed to form a slurry, which was then coated on carbon cloth for use as the positive electrode of a zinc-air battery.
[0097] Example 7
[0098] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0099] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0100] (2) Weigh 0.9 g of cobalt acetylacetonate and 1.3 g of methionine respectively and mix until the color is fully uniform, then weigh 4.5 g of sodium chloride and mix again, and finally weigh 10 g of zinc chloride and add to mix thoroughly to form a mixture solid with uniform color;
[0101] (3) annealing the mixture solid in a tube furnace under the protection of inert gas helium, with an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0102] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0103] (5) 10 mg of the prepared bifunctional catalyst, 1000 μL of water, 1000 μL of ethanol, and 100 μL of Nafion were mixed to form a slurry, which was then coated on carbon paper for use as the positive electrode of a zinc-air battery.
[0104] Example 8
[0105] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0106] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0107] (2) Weigh 1.4 g of manganese acetylacetonate and 0.5 g of sodium dodecyl sulfate respectively and mix them until the color is fully uniform. Weigh 3.5 g of sodium chloride again and mix them. Finally, weigh 8 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0108] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0109] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0110] (5) 6 mg of the prepared bifunctional catalyst, 500 μL of water, 980 μL of ethanol, and 80 μL of Nafion were mixed to form a slurry, which was then applied on nickel foam for use as the positive electrode of a zinc-air battery.
[0111] Example 9
[0112] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0113] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0114] (2) Weigh 1 g of nickel acetylacetonate and 1 g of methionine respectively and mix until the color is fully uniform, then weigh 5 g of sodium chloride and mix again, and finally weigh 5 g of zinc chloride and add to mix thoroughly to form a solid mixture with uniform color;
[0115] (3) annealing the mixture solid in a tube furnace under the protection of inert gas argon at an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0116] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0117] (5) 3 mg of the prepared bifunctional catalyst, 400 μL of water, 400 μL of ethanol, and 100 μL of Nafion were mixed to form a slurry, which was then coated on carbon paper for use as the positive electrode of a zinc-air battery.
[0118] Example 10
[0119] In this embodiment, the preparation process of the oxygen-electric bifunctional electrocatalyst includes the following steps:
[0120] (1) Zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt;
[0121] (2) Weigh 1.5 g of copper acetylacetonate and 1 g of thiourea respectively and mix them until the color is fully uniform. Then weigh 6 g of sodium chloride and mix them again. Finally, weigh 6 g of zinc chloride and add them to mix thoroughly to form a solid mixture with uniform color.
[0122] (3) annealing the mixture solid in a tube furnace under the protection of inert gas nitrogen, with an annealing heating rate of 10° C. / min, heating to 900° C., and keeping the temperature for 2 h to obtain a high-temperature black solid;
[0123] (4) The high-temperature black solid is thoroughly washed with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst.
[0124] (5) 10 mg of the prepared bifunctional catalyst, 980 μL of water, 980 μL of ethanol, and 100 μL of Nafion were mixed to form a slurry, which was then applied on nickel foam for use as the positive electrode of a zinc-air battery.
[0125] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method, characterized in that: The steps include: S1: zinc chloride and sodium chloride are selected as binary eutectic low-temperature molten salt; S2: weighing the metal-containing carbon source and sulfur source in sequence and mixing them evenly, weighing zinc chloride and sodium chloride, adding them to the mixture and mixing them evenly again to obtain a precursor with uniform color; S3: annealing the uniformly mixed precursor obtained by grinding at 700-1000° C. for 1-3 h under the protection of an inert gas to obtain a high-temperature solid product; S4: washing the high-temperature solid product with deionized water to obtain the oxygen-electricity bifunctional electrocatalyst; S5: The prepared bifunctional catalyst, water, ethanol and Nafion are mixed in a certain proportion to form a slurry, which is then coated on a conductive substrate for use as the positive electrode of a zinc-air battery.
2. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The zinc chloride and sodium chloride described in S1 have dual functions, namely, serving as carbon material carriers, and zinc cations serving as reactants to participate in the reaction to form zinc sulfide, and the ratio of zinc chloride to sodium chloride is 1-10:1-10.
3. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The metal-containing carbon source described in S2 is at least one or more of iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate and manganese acetylacetonate.
4. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The sulfur source described in S2 is at least one sulfur-containing organic compound selected from thiourea, methionine, and sodium dodecyl sulfate; the mass ratio of the metal-containing carbon source, sulfur source, zinc chloride, and sodium chloride is: 0.1-1:0.1-2:1-10:1-10.
5. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: S3 The inert gas is one of nitrogen, argon or helium.
6. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The annealing heating rate in S3 is 2-15°C / min, the temperature is raised to 700-1000°C, and the temperature is kept for 1-3h.
7. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The ratio of the catalyst, water, ethanol and Nafion described in S5 is 2-10:500-1500:500-1500:30-100, wherein the unit of the catalyst is mg, and the unit of water, ethanol and Nafion is μL.
8. The method for preparing oxygen-electric bifunctional electrocatalyst by low-temperature molten salt method according to claim 1, characterized in that: The conductive substrate to be coated in S5 is one of carbon cloth, carbon paper, nickel foam and copper foam.
9. The oxygen-electric bifunctional electrocatalyst prepared by the low-temperature molten salt method according to any one of claims 1 to 8.
10. Use of the coated conductive substrate according to claim 9 in preparing a high-stability zinc-air battery.
Citation Information
Patent Citations
P-O doped Fe-N-C nanosheet and preparation method thereof
CN110635140A
Biochemical energy conversion cell
US20140373920A1